2012
DOI: 10.1182/blood-2011-06-362830
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of non-Hodgkin lymphoma, leukemia, and myeloma in patients with diabetes mellitus type 2: a meta-analysis of observational studies

Abstract: Hematologic malignancies are a heterogeneous group of conditions with an unclear etiology. We hypothesized that diabetes mellitus type 2 is associated with increased risk of developing lymphoma, leukemia, and myeloma. A literature search identified 26 studies (13 casecontrol and 13 cohort studies) evaluating such an association. Outcome was calculated as the odds ratio (OR) using a random effects model. Heterogeneity and publication bias were evaluated using the I 2 index and the trim-and-fill analysis, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 41 publications
3
142
1
3
Order By: Relevance
“…In addition, exposure to a wide range of toxins as well as type 2 diabetes (T2D) and obesity have been suggested as important mediators of the complex process of myelomagenesis (Alexander et al 2007, Lope et al 2008, Wallin & Larsson 2011. Among these latter preventable factors, T2D has attracted significant attention since it has been consistently identified as a medical condition frequently found in MM patients (Khan et al 2008, Richardson et al 2009, Castillo et al 2012 and it is thought to influence the myelomagenesis through hyperglycaemia and insulin-dependent and -independent mechanisms (Xu et al 2014). In a recent well-powered meta-analysis, Castillo et al (2012) observed that T2D was significantly associated with an increased risk of developing the disease (Castillo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, exposure to a wide range of toxins as well as type 2 diabetes (T2D) and obesity have been suggested as important mediators of the complex process of myelomagenesis (Alexander et al 2007, Lope et al 2008, Wallin & Larsson 2011. Among these latter preventable factors, T2D has attracted significant attention since it has been consistently identified as a medical condition frequently found in MM patients (Khan et al 2008, Richardson et al 2009, Castillo et al 2012 and it is thought to influence the myelomagenesis through hyperglycaemia and insulin-dependent and -independent mechanisms (Xu et al 2014). In a recent well-powered meta-analysis, Castillo et al (2012) observed that T2D was significantly associated with an increased risk of developing the disease (Castillo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among these latter preventable factors, T2D has attracted significant attention since it has been consistently identified as a medical condition frequently found in MM patients (Khan et al 2008, Richardson et al 2009, Castillo et al 2012 and it is thought to influence the myelomagenesis through hyperglycaemia and insulin-dependent and -independent mechanisms (Xu et al 2014). In a recent well-powered meta-analysis, Castillo et al (2012) observed that T2D was significantly associated with an increased risk of developing the disease (Castillo et al 2012). This finding concurs with those previously reported in several epidemiological studies that showed a high incidence of T2D among MM patients ranging between 11 and 22% (Richardson et al 2006, Badros et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] As already shown in several meta-analyses, patients with type 2 diabetes have an elevated risk of pancreatic, bladder, hepatocellular, ovarian, breast, endometrial, renal, gastric, colorectal and thyroid cancers and, moreover, of non-Hodgkin's lymphoma, leukaemia and myeloma. [14][15][16][17][18][19][20][21][22][23][24] The underlying mechanisms are subject to ongoing investigations, but relevant factors appear to be hyperinsulinaemia due to either insulin resistance or insulin-based therapy, hyperglycaemia, hyperlipidaemia, altered levels of circulating oestrogens and androgens, and inflammatory processes, which have all been associated with an increase in cancer incidence and/ or cancer mortality.…”
Section: Introductionmentioning
confidence: 99%
“…An association between NHL and diabetes mellitus has been reported (7). Moreover, cigarette smoking is associated with an increased risk of NHL (8).…”
Section: Discussionmentioning
confidence: 99%